Veteran employment : lessons from the 100,000 Jobs Mission - Hall, Kimberly Curry; Harrell, Margaret C.; Bicksler, Barbara A.; Stewart, Robert; Fisher, Michael P. (RAND, 2014)
Eleven companies cofounded the 100,000 Jobs Mission in 2011 to promote veteran employment, with a goal of hiring 100,000 veterans by 2020. The coalition has grown to over 175 companies, which have exceeded the initial goal and are now on track to hire 200,000 veterans by the end of 2014. These companies represent nearly every U.S. industry and vary in size, geographic location, and in the types of veterans they hire. Reflecting on the first three years of operation, JPMorgan Chase & Co. asked the RAND Corporation to capture the lessons and experiences from the 100,000 Jobs Mission to identify further improvements to veteran employment opportunities. RAND researchers conducted qualitative interviews with representatives of a sample of member companies, delving into the ways they recruit and hire veterans, help veterans transition into their new jobs, and manage and develop veteran employees and the value veterans bring as employees. Interviewees pointed out that veterans are most noted for their leadership skills and teamwork; for their flexibility and ability to work in a fast-paced, changing environment without undue stress; for their dependability, integrity, and loyalty; and for their experience working in a culturally diverse or global environment. This research also explored the challenges to hiring and employing veterans and provides recommendations to assist employers and promote veteran employment opportunities more broadly.